Utilization of Nonviral Sequences for Minus-Strand DNA Transfer and Gene Reconstitution during Retroviral Replication - Cheslock, Sara Rasmussen (American Society for Microbiology, 2000)
Minus-strand DNA transfer, an essential step in retroviral reverse transcription, is mediated by the two repeat (R) regions in the viral genome. It is unclear whether R simply serves as a homologous sequence to mediate the strand transfer or contains specific sequences to promote strand transfer. To test the hypothesis that the molecular mechanism by which R mediates strand transfer is based on homology rather than specific sequences, we examined whether nonviral sequences can be used to facilitate minus-strand DNA transfer. The green fluorescent protein (GFP) gene was divided into GF and FP fragments, containing the 5′ and 3′ portions of GFP, respectively, with an overlapping F fragment (85 bp). FP and GF were inserted into the 5′ and 3′ long terminal repeats, respectively, of a murine leukemia virus-based vector. Utilization of the F fragment to mediate minus-strand DNA transfer should reconstitute GFP during reverse transcription. Flow cytometry analyses demonstrated that GFP was expressed in 73 to 92% of the infected cells, depending on the structure of the viral construct. This indicated that GFP was reconstituted at a high frequency; molecular characterization further confirmed the accurate reconstitution of GFP. These data indicated that nonviral sequences could be used to efficiently mediate minus-strand DNA transfer. Therefore, placement and homology, not specific sequence context, are the important elements in R for minus-strand DNA transfer. In addition, these experiments demonstrate that minus-strand DNA transfer can be used to efficiently reconstitute genes for gene therapy applications.